A low dielectric insulating material suitable for 10kv cables and a method of making the same
Patent Information
- Application Number
- CN202611476308.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]现有技术仍存在以下不足:纳米填料在聚乙烯基体中的分散性差,易团聚形成缺陷;小分子电压稳定剂易迁移析出,长效稳定性不足;为了解决上述问题,本发明提供一种适用于10kV电缆的低介电绝缘材料及其制备方法,旨在通过接枝型电压稳定剂与改性纳米填料的协同作用,同步解决迁移性、分散性及介电性能优化的问题
1、本发明采用非极性聚乙烯蜡润滑体系、改性纳米粘土及硅烷改性纳米氧化锌,消除无机填料表面极性羟基与界面缺陷;同时采用接枝改性低密度聚乙烯替代小分子掺杂体系,避免大量极性小分子富集界面;各组分协同实现材料低介电常数、低介质损耗特性;
Smart Images

Figure CN123004010A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer material preparation technology, specifically relating to a low dielectric insulating material suitable for 10kV cables and its preparation method. Background Technology
[0002] Cross-linked polyethylene (XLPE) has become the mainstream insulation material for power cables due to its excellent insulation properties, good processing characteristics, and mechanical properties. For 10kV power cables, in addition to meeting basic requirements such as tensile strength and elongation at break, the insulation material also needs to maintain low dielectric loss and stable aging resistance under thermal, electrical, and damp heat stress.
[0003] To suppress space charge and electrical aging, existing technologies mainly employ two modification approaches:
[0004] One approach involves introducing inorganic nanofillers to construct charge traps, commonly using composites of fillers such as nano-zinc oxide, nano-silica, or boron nitride. For example, Chinese patent application CN104231395A discloses a water-tree resistant polyethylene nanocomposite material that uses vinyltrimethoxysilane-modified nano-silica as a single filler, allowing the nanoparticles to be uniformly dispersed in the matrix, thus achieving excellent water-tree resistance. However, this approach only introduces a single type of inorganic particle, resulting in relatively concentrated interfacial properties. When the filler content is too low, the interfacial regulation effect may be insufficient, and the space charge binding ability may be limited; conversely, when the filler content is too high, problems such as interfacial polarization, increased dielectric loss, and decreased mechanical properties can easily occur.
[0005] Secondly, small-molecule aromatic voltage stabilizers are doped into the polyethylene matrix to capture high-energy charge carriers through conjugated structures. However, the compatibility between small-molecule voltage stabilizers and polyethylene is limited. Under high processing temperature and long-term operation conditions, they are prone to migration, precipitation and volatilization. After long-term aging, the voltage stabilization effect decays rapidly, making it difficult to meet the long-term operation requirements of cables.
[0006] Therefore, it is necessary to develop a low-dielectric insulation material with synergistic components, low dielectric and low loss characteristics, long-term voltage stability, and suitability for 10kV cables. Summary of the Invention
[0007] The existing technology still has the following shortcomings: the nanofiller has poor dispersibility in the polyethylene matrix and is prone to agglomeration and formation of defects; small molecule voltage stabilizers are prone to migration and precipitation, and have insufficient long-term stability. In order to solve the above problems, the present invention provides a low dielectric insulating material suitable for 10kV cables and its preparation method, aiming to solve the problems of migration, dispersibility and dielectric performance optimization at the same time through the synergistic effect of grafted voltage stabilizers and modified nanofillers.
[0008] To achieve the objectives of this invention, the following technical solution is adopted: In a first aspect, the present invention provides a low-dielectric insulating material suitable for 10kV cables, comprising the following components in parts by weight: 100 parts of low-density polyethylene, 0.3-0.8 parts of graft-modified low-density polyethylene, 0.2-0.6 parts of modified nano-clay, 0.2-0.8 parts of silane-modified nano-zinc oxide, 0.12-0.25 parts of antioxidant, 1.2-1.6 parts of peroxide crosslinking agent, and 0.08-0.25 parts of lubricant; The grafted modified low-density polyethylene is prepared by reacting 3-aminobenzoic acid with dodecenylsuccinic anhydride to generate an intermediate, which is then melt-grafted onto polyethylene.
[0009] By adopting the above technical solution, low-density polyethylene is used as the matrix material to ensure insulation performance; grafted modified low-density polyethylene is used as a covalently bonded voltage stabilizer, which is anchored to the polyethylene molecular chain through chemical bonds, solving the problem of easy migration and precipitation of small molecule stabilizers under long-term electric field and thermal stress, and endowing the material with long-term stable electrical resistance; modified nano-clay and silane-modified nano-zinc oxide are used as inorganic nanofillers, which work together to play a dual role of physical cross-linking points and charge traps, effectively inhibiting the accumulation of space charge; the components work synergistically within the limited ratio range to effectively reduce the dielectric constant of the material and improve the breakdown strength and resistance to electrical aging.
[0010] Furthermore, the preparation method of the grafted modified low-density polyethylene includes the following steps: 3-Aminobenzoic acid and dodecenylsuccinic anhydride were added to anhydrous tetrahydrofuran and reacted at 60-70°C for 2-3 hours under nitrogen protection to obtain an intermediate. The intermediate, dicumyl peroxide, and low-density polyethylene were mixed, melt-grafted, water-cooled, and granulated to obtain grafted modified low-density polyethylene.
[0011] By adopting the above technical solution, the ring-opening reaction of amino groups and acid anhydrides occurs under mild reaction conditions and a nitrogen atmosphere, preserving the carbon-carbon double bond and aromatic conjugated structure at the distal end of the intermediate molecule, thus ensuring the active sites of the subsequent melt grafting reaction. Using dicumyl peroxide as an initiator, the voltage stabilizer containing the aromatic ring structure is covalently anchored to the polyethylene molecular chain through melt grafting. The grafting efficiency is high, the process is simple to operate, and it is convenient for continuous industrial production.
[0012] Furthermore, the molar ratio of 3-aminobenzoic acid to dodecenylsuccinic anhydride is 1:(1.05~1.1).
[0013] By adopting the above technical solution, within this molar ratio range, dodecenylsuccinic anhydride is in slight excess relative to 3-aminobenzoic acid, ensuring that the amino group on 3-aminobenzoic acid is fully reacted, reducing the residue of small molecules of free 3-aminobenzoic acid, improving the intermediate yield, and avoiding a large amount of unreacted anhydride residue. The intermediate at this ratio has an aromatic ring voltage-stable structure, flexible long-chain alkyl compatible segments, and active double bonds that can be grafted, providing a structural basis for subsequent grafting with polyethylene.
[0014] Furthermore, the mass ratio of the intermediate, dicumyl peroxide, to low-density polyethylene is (8~12):(0.06~0.1):100.
[0015] By adopting the above technical solution, within this mass ratio range, a sufficient concentration of functional intermediates can be ensured to participate in the grafting reaction, constructing an effective deep trap energy level density, thereby suppressing electrical tree initiation and space charge accumulation; at the same time, the amount of dicumyl peroxide used is only used to initiate double bond grafting, avoiding excessive cross-linking of polyethylene caused by excessive initiator.
[0016] Furthermore, the preparation method of the modified nanoclay includes the following steps: Add octadecyl glycol polyethylene glycol ether to anhydrous ethanol and stir at 60-65°C; add nano-clay and ultrasonically disperse for 40-50 min; let stand for 1.5-2 h and then dry to obtain modified nano-clay.
[0017] By adopting the above technical solution, the surface of the nano-clay is modified by coating it with the nonionic surfactant octadecyl glycol ether, which reduces the surface energy of the clay sheets and inhibits the tendency of nanoparticles to aggregate. Ultrasonic dispersion treatment further promotes the dispersion of clay in the liquid phase, so that the modified nano-clay can be uniformly dispersed when melt-blended with polyethylene, thereby giving full play to its function as a physical crosslinking point and a space charge trap.
[0018] Furthermore, the mass ratio of the octadecyl glycol polyethylene glycol ether to the nano-clay is (1.5~2):100.
[0019] By adopting the above technical solution, within this mass ratio range, the amount of octadecyl alcohol polyethylene glycol ether is moderate, which can form a coating layer on the surface of nano clay, effectively shielding the strong polar interaction between clay sheets and preventing secondary agglomeration during the drying process.
[0020] Furthermore, the silane-modified nano zinc oxide is prepared by modifying nano zinc oxide with a particle size of 10~50nm using vinyltrimethoxysilane.
[0021] By adopting the above technical solution, vinyltrimethoxysilane introduces organic compatibility groups on the surface of nano zinc oxide, which effectively improves the interfacial compatibility between inorganic nanoparticles and polyethylene matrix; the particle size range of 10~50nm ensures sufficient interfacial area to construct shallow energy level charge traps and exert the interfacial trap effect.
[0022] Further, the antioxidant is 4,4'-thiobis(2-tert-butyl-5-methylphenol) or 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].
[0023] By adopting the above technical solutions, the two thiobisphenol antioxidants possess free radical scavenging and peroxide decomposition capabilities, and their inhibitory effect on peroxide crosslinking is weaker compared to hindered phenolic antioxidants. Both antioxidants exhibit good compatibility with the polyethylene matrix, inhibiting thermo-oxidative degradation during material processing and long-term service, protecting the interface structure between the grafted modified components and fillers, and maintaining the long-term stability of the insulating material.
[0024] Furthermore, the peroxide crosslinking agent is dicumyl peroxide; the lubricant is polyethylene wax.
[0025] By adopting the above technical solution, dicumyl peroxide as a crosslinking agent can initiate chemical crosslinking reactions between polyethylene molecular chains to form a three-dimensional network structure, thereby improving the heat distortion temperature and creep resistance of the insulating material. Polyethylene wax is a non-polar polyolefin structure that is homologous and compatible with the low-density polyethylene matrix. As a lubricant, it can improve melt flowability and promote the dispersion of inorganic fillers without negatively affecting the insulation performance.
[0026] Secondly, the present invention provides a method for preparing a low-dielectric insulating material suitable for 10kV cables, comprising the following steps: S1: Low-density polyethylene, grafted low-density polyethylene, modified nano clay, silane-modified nano zinc oxide, antioxidant and lubricant are put into a high-speed mixer and mixed at 60~80℃ for 5~10 minutes to obtain a premix. S2: The premixed material and peroxide crosslinking agent are added to a twin-screw extruder. The barrel temperature is 140~170℃ and the screw speed is 220~300rpm. After water cooling, pelletizing and drying, a low dielectric insulating material is obtained.
[0027] By adopting the above technical solution, the low-temperature premixing in step S1 achieves the initial uniform dispersion of each material, and the cross-linking reaction of dicumyl peroxide in step S2 is initiated within a suitable temperature range to obtain a moderate degree of cross-linking. The resulting low-dielectric insulating material can be cross-linked in the cable vulcanization process after being extruded onto the conductor. The entire process is simple, continuous, and efficient, and is suitable for large-scale industrial production.
[0028] In summary, the beneficial effects of this invention are: 1. This invention employs a non-polar polyethylene wax lubrication system, modified nano-clay, and silane-modified nano-zinc oxide to eliminate polar hydroxyl groups and interface defects on the surface of inorganic fillers; at the same time, it uses grafted modified low-density polyethylene to replace the small molecule doping system to avoid the enrichment of a large number of polar small molecules at the interface; the components work together to achieve the material's low dielectric constant and low dielectric loss characteristics. 2. This invention simultaneously introduces an organic aromatic conjugate voltage-stabilizing structure and a two-level charge trapping system: the aromatic structure in the grafted modified low-density polyethylene can capture high-energy charge carriers and inhibit the growth of electric trees; the modified nano-clay provides deep-level traps and the silane-modified nano-zinc oxide provides shallow-level traps. The two work together to inhibit the accumulation of space charge and improve the insulation breakdown strength. Attached Figure Description
[0029] Figure 1 This is the infrared spectrum of graft-modified low-density polyethylene. Detailed Implementation
[0030] The present invention will be further described below with reference to specific embodiments.
[0031] Unless otherwise specified, the experimental methods used in the following examples and comparative examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples and comparative examples are commercially available.
[0032] Preparation example: Preparation of silane-modified nano zinc oxide Preparation Example 1 Nano-zinc oxide with a particle size of 10~50nm was vacuum dried at 100℃ for 4h to obtain dried nano-zinc oxide; 2g vinyltrimethoxysilane, 950g ethanol and 50g water were mixed, the pH value was adjusted to 4.5 with glacial acetic acid, and the mixture was reacted at 30℃ for 45min. 100g of dried nano-zinc oxide was added, stirred for 15min, heated to 80℃ and reacted for another 60min. After cooling, the mixture was filtered, washed with anhydrous ethanol, and vacuum dried at 65℃ for 12h to obtain silane-modified nano-zinc oxide.
[0033] Preparation Examples 2-4: Preparation of Modified Nanoclay Preparation Example 2 Add 2g of octadecyl polyethylene glycol ether to anhydrous ethanol and stir at 65℃ until completely dissolved; add 100g of nano clay and ultrasonically disperse for 40min; let stand for 2h and then dry, remove ethanol solvent under reduced pressure, and dry at 95℃ for 36h to obtain modified nano clay.
[0034] Preparation Example 3 1.8g of octadecyl polyethylene glycol ether was added to anhydrous ethanol and stirred at 60℃ until completely dissolved; 100g of nano clay was added and ultrasonically dispersed for 50min; after standing for 2h, it was dried, the ethanol solvent was removed under reduced pressure, and it was dried at 95℃ for 36h to obtain modified nano clay.
[0035] Preparation Example 4 1.6 g of octadecyl polyethylene glycol ether was added to anhydrous ethanol and stirred at 60 °C until completely dissolved; 100 g of nano clay was added and ultrasonically dispersed for 50 min; after standing for 1.5 h, it was dried, the ethanol solvent was removed under reduced pressure, and it was dried at 95 °C for 36 h to obtain modified nano clay.
[0036] Preparation Examples 5-8: Preparation of Graft-Modified Low-Density Polyethylene Preparation Example 5 0.1 mol of 3-aminobenzoic acid and 0.108 mol of dodecenylsuccinic anhydride were added to 300 mL of anhydrous tetrahydrofuran. The mixture was heated to 65 °C and stirred for 3 h under nitrogen protection. After the reaction was completed, the solvent was removed by vacuum distillation to obtain an intermediate. 10 g of the intermediate, 0.08 g of dicumyl peroxide and 100 g of low-density polyethylene were added to a high-speed mixer for uniform premixing. The grafting reaction was carried out using a twin-screw extruder. The processing temperature was controlled at 160 °C and the screw speed was 250 rpm. The extruded melt was water-cooled and granulated, then vacuum dried and degassed under vacuum at a constant temperature to obtain grafted modified low-density polyethylene.
[0037] Figure 1 This is the infrared spectrum of graft-modified low-density polyethylene. Figure 1 It can be seen that the grafted product is at 3300cm -1 NH stretching absorption occurs at 2918 cm⁻¹. -1 2850cm -1 1460cm -1 and 720cm -1 The area exhibits characteristic absorption of the methylene group at 1645 cm⁻¹. -1 C=O related absorption occurs at 1600 cm⁻¹. -1 A benzene ring-related absorption is observed nearby, at 1535 cm⁻¹. -1 The presence of NH bending vibration absorption indicates the successful synthesis of graft-modified low-density polyethylene.
[0038] Preparation Example 6 0.1 mol of 3-aminobenzoic acid and 0.105 mol of dodecenylsuccinic anhydride were added to 300 mL of anhydrous tetrahydrofuran. The mixture was heated to 70 °C and stirred for 2 h under nitrogen protection. After the reaction was completed, the solvent was removed by vacuum distillation to obtain an intermediate. 9.5 g of the intermediate, 0.1 g of dicumyl peroxide and 100 g of low-density polyethylene were added to a high-speed mixer for uniform premixing. The grafting reaction was carried out using a twin-screw extruder. The processing temperature was controlled at 160 °C and the screw speed was 250 rpm. The extruded melt was water-cooled and granulated, then vacuum dried and degassed under vacuum at a constant temperature to obtain grafted modified low-density polyethylene.
[0039] Preparation Example 7 0.1 mol of 3-aminobenzoic acid and 0.11 mol of dodecenylsuccinic anhydride were added to 300 mL of anhydrous tetrahydrofuran. The mixture was heated to 60 °C and stirred for 3 h under nitrogen protection. After the reaction was completed, the solvent was removed by vacuum distillation to obtain an intermediate. 8 g of the intermediate, 0.06 g of dicumyl peroxide, and 100 g of low-density polyethylene were added to a high-speed mixer for uniform premixing. The grafting reaction was carried out using a twin-screw extruder. The processing temperature was controlled at 160 °C and the screw speed was 250 rpm. The extruded melt was water-cooled and granulated, then vacuum dried and degassed under vacuum at a constant temperature to obtain grafted modified low-density polyethylene.
[0040] Preparation Example 8 0.1 mol of 3-aminobenzoic acid and 0.11 mol of dodecenylsuccinic anhydride were added to 300 mL of anhydrous tetrahydrofuran. The mixture was heated to 70 °C and stirred for 3 h under nitrogen protection. After the reaction was completed, the solvent was removed by vacuum distillation to obtain an intermediate. 11.5 g of the intermediate, 0.08 g of dicumyl peroxide and 100 g of low-density polyethylene were added to a high-speed mixer for uniform premixing. The grafting reaction was carried out using a twin-screw extruder. The processing temperature was controlled at 160 °C and the screw speed was 250 rpm. The extruded melt was water-cooled and granulated, then vacuum dried and degassed under vacuum at a constant temperature to obtain grafted modified low-density polyethylene.
[0041] Examples 1-5: Preparation of low-dielectric insulation materials suitable for 10kV cables Example 1 This embodiment of a low-dielectric insulation material suitable for 10kV cables is composed of the following components in parts by weight: 100 parts low-density polyethylene, 0.6 parts grafted modified low-density polyethylene, 0.5 parts modified nano-clay, 0.5 parts silane-modified nano-zinc oxide, 0.2 parts antioxidant, 1.2 parts peroxide crosslinking agent, and 0.15 parts lubricant; The grafted modified low-density polyethylene is the grafted modified low-density polyethylene prepared in Preparation Example 5; The modified nanoclay is the modified nanoclay prepared in Preparation Example 2; The silane-modified nano zinc oxide is the silane-modified nano zinc oxide prepared in Preparation Example 1; The antioxidant is 4,4'-thiobis(2-tert-butyl-5-methylphenol); The peroxide crosslinking agent is dicumyl peroxide; The lubricant is polyethylene wax.
[0042] This embodiment describes a method for preparing a low-dielectric insulating material suitable for 10kV cables, with the following specific steps: S1: Low-density polyethylene, grafted low-density polyethylene, modified nano clay, silane-modified nano zinc oxide, antioxidant and lubricant are put into a high-speed mixer and mixed at 70°C for 10 minutes to obtain a premix. S2: The premixed material and peroxide crosslinking agent are added to a twin-screw extruder. The barrel temperature is 150℃ and the screw speed is 250rpm. After water cooling, pelletizing, and drying, a low-dielectric insulating material is obtained.
[0043] Example 2 This embodiment of a low-dielectric insulation material suitable for 10kV cables is composed of the following components in parts by weight: 100 parts low-density polyethylene, 0.4 parts graft-modified low-density polyethylene, 0.4 parts modified nano-clay, 0.6 parts silane-modified nano-zinc oxide, 0.18 parts antioxidant, 1.4 parts peroxide crosslinking agent, and 0.1 parts lubricant; The grafted modified low-density polyethylene is the grafted modified low-density polyethylene prepared in Preparation Example 5; The modified nanoclay is the modified nanoclay prepared in Preparation Example 2; The silane-modified nano zinc oxide is the silane-modified nano zinc oxide prepared in Preparation Example 1; The antioxidant is 4,4'-thiobis(2-tert-butyl-5-methylphenol); The peroxide crosslinking agent is dicumyl peroxide; The lubricant is polyethylene wax.
[0044] This embodiment describes a method for preparing a low-dielectric insulating material suitable for 10kV cables, with the following specific steps: S1: Low-density polyethylene, grafted low-density polyethylene, modified nano clay, silane-modified nano zinc oxide, antioxidant and lubricant are put into a high-speed mixer and mixed at 65°C for 8 minutes to obtain a premix. S2: The premixed material and peroxide crosslinking agent are added to a twin-screw extruder. The barrel temperature is 160℃ and the screw speed is 260rpm. After water cooling, pelletizing, and drying, a low-dielectric insulating material is obtained.
[0045] Example 3 This embodiment of a low-dielectric insulation material suitable for 10kV cables is composed of the following components in parts by weight: 100 parts low-density polyethylene, 0.8 parts grafted modified low-density polyethylene, 0.35 parts modified nano-clay, 0.75 parts silane-modified nano-zinc oxide, 0.22 parts antioxidant, 1.25 parts peroxide crosslinking agent, and 0.2 parts lubricant; The grafted modified low-density polyethylene is the grafted modified low-density polyethylene prepared in Preparation Example 6; The modified nanoclay is the modified nanoclay prepared in Preparation Example 3; The silane-modified nano zinc oxide is the silane-modified nano zinc oxide prepared in Preparation Example 1; The antioxidant is 4,4'-thiobis(2-tert-butyl-5-methylphenol); The peroxide crosslinking agent is dicumyl peroxide; The lubricant is polyethylene wax.
[0046] This embodiment describes a method for preparing a low-dielectric insulating material suitable for 10kV cables, with the following specific steps: S1: Low-density polyethylene, grafted low-density polyethylene, modified nano clay, silane-modified nano zinc oxide, antioxidant and lubricant are put into a high-speed mixer and mixed at 80°C for 5 minutes to obtain a premix. S2: The premixed material and peroxide crosslinking agent are added to a twin-screw extruder. The barrel temperature is 140℃ and the screw speed is 300rpm. After water cooling, pelletizing, and drying, a low-dielectric insulating material is obtained.
[0047] Example 4 This embodiment of a low-dielectric insulation material suitable for 10kV cables is composed of the following components in parts by weight: 100 parts low-density polyethylene, 0.5 parts grafted modified low-density polyethylene, 0.6 parts modified nano-clay, 0.7 parts silane modified nano-zinc oxide, 0.25 parts antioxidant, 1.5 parts peroxide crosslinking agent, and 0.16 parts lubricant; The grafted modified low-density polyethylene is the grafted modified low-density polyethylene prepared in Preparation Example 6; The modified nanoclay is the modified nanoclay prepared in Preparation Example 4; The silane-modified nano zinc oxide is the silane-modified nano zinc oxide prepared in Preparation Example 1; The antioxidant is 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; The peroxide crosslinking agent is dicumyl peroxide; The lubricant is polyethylene wax.
[0048] This embodiment describes a method for preparing a low-dielectric insulating material suitable for 10kV cables, with the following specific steps: S1: Low-density polyethylene, grafted low-density polyethylene, modified nano clay, silane-modified nano zinc oxide, antioxidant and lubricant are put into a high-speed mixer and mixed at 70°C for 8 minutes to obtain a premix. S2: The premixed material and peroxide crosslinking agent are added to a twin-screw extruder. The barrel temperature is 150℃ and the screw speed is 220rpm. After water cooling, pelletizing, and drying, a low-dielectric insulating material is obtained.
[0049] Example 5 This embodiment of a low-dielectric insulation material suitable for 10kV cables is composed of the following components in parts by weight: 100 parts low-density polyethylene, 0.7 parts grafted modified low-density polyethylene, 0.55 parts modified nano-clay, 0.6 parts silane-modified nano-zinc oxide, 0.2 parts antioxidant, 1.2 parts peroxide crosslinking agent, and 0.2 parts lubricant; The grafted modified low-density polyethylene is the grafted modified low-density polyethylene prepared in Preparation Example 5; The modified nanoclay is the modified nanoclay prepared in Preparation Example 3; The silane-modified nano zinc oxide is the silane-modified nano zinc oxide prepared in Preparation Example 1; The antioxidant is 4,4'-thiobis(2-tert-butyl-5-methylphenol); The peroxide crosslinking agent is dicumyl peroxide; The lubricant is polyethylene wax.
[0050] This embodiment describes a method for preparing a low-dielectric insulating material suitable for 10kV cables, with the following specific steps: S1: Low-density polyethylene, grafted low-density polyethylene, modified nano clay, silane-modified nano zinc oxide, antioxidant and lubricant are put into a high-speed mixer and mixed at 70°C for 5 minutes to obtain a premix. S2: The premixed material and peroxide crosslinking agent are added to a twin-screw extruder. The barrel temperature is 150℃ and the screw speed is 300rpm. After water cooling, pelletizing, and drying, a low-dielectric insulating material is obtained.
[0051] Comparative Examples 1-5: Preparation of Insulating Materials Comparative Example 1 The difference from Example 1 is that this comparative example does not contain grafted modified low-density polyethylene, but is otherwise the same as Example 1.
[0052] Comparative Example 2 The difference from Example 1 is that this comparative example uses an equal amount of 3-aminobenzoic acid instead of grafted modified low-density polyethylene, while the rest is the same as in Example 1.
[0053] Comparative Example 3 The difference from Example 1 is that this comparative example does not add silane-modified nano zinc oxide, but is otherwise the same as Example 1.
[0054] Comparative Example 4 The difference from Example 1 is that no modified nano-clay is added in this comparative example, but everything else is the same as in Example 1.
[0055] Comparative Example 5 The difference from Example 1 is that this comparative example uses an equal amount of nano-clay instead of modified nano-clay, while everything else is the same as in Example 1.
[0056] Related performance tests The insulating materials prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to relevant performance tests, and the test results are shown in Table 1.
[0057] Table 1 Test Results
[0058] As can be seen from the data in Table 1: The insulating materials prepared in Examples 1-5 have a relative permittivity < 2.2 and a dielectric loss factor ≤ 2.5 × 10⁻⁶. -4 It possesses excellent low dielectric properties; DC breakdown strength >35kV / mm, and excellent electrical withstand performance.
[0059] Comparative Example 1, without the addition of graft-modified low-density polyethylene, lacks covalently bonded voltage-stabilizing units, resulting in space charge accumulation and performance degradation.
[0060] Comparative Example 2 uses small molecule 3-aminobenzoic acid instead of graft-modified low-density polyethylene; small molecules are easy to migrate, resulting in increased dielectric loss and lower breakdown strength than in the examples.
[0061] Comparative Examples 3 and 4 use only a single inorganic filler, lacking the synergistic effect of energy level charge traps, resulting in a decreased space charge suppression effect and a lower breakdown strength than the examples.
[0062] Comparative Example 5 used unmodified original nano-clay. The polar groups on the clay surface induced interfacial polarization, which increased dielectric loss. This confirmed that surface modification of octadecyl alcohol polyethylene glycol ether can weaken interfacial polarization and achieve a balance between low dielectric and filler dispersion.
[0063] In summary, the components of this invention work synergistically to achieve a combination of low dielectric constant, low dielectric loss, and effective suppression of space charge within a defined ratio range.
[0064] The present invention has been described above by way of example. It should be noted that any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort without departing from the core of the present invention fall within the protection scope of the present invention.
Claims
1. A low-dielectric insulating material suitable for 10kV cables, characterized in that, It consists of the following components in parts by mass: 100 parts of low-density polyethylene, 0.3-0.8 parts of graft-modified low-density polyethylene, 0.2-0.6 parts of modified nano-clay, 0.2-0.8 parts of silane-modified nano-zinc oxide, 0.12-0.25 parts of antioxidant, 1.2-1.6 parts of peroxide crosslinking agent, and 0.08-0.25 parts of lubricant; The grafted modified low-density polyethylene is prepared by reacting 3-aminobenzoic acid with dodecenylsuccinic anhydride to generate an intermediate, which is then melt-grafted onto polyethylene.
2. The low-dielectric insulation material suitable for 10kV cables according to claim 1, characterized in that, The preparation method of the grafted modified low-density polyethylene includes the following steps: 3-Aminobenzoic acid and dodecenylsuccinic anhydride were added to anhydrous tetrahydrofuran and reacted at 60-70°C for 2-3 hours under nitrogen protection to obtain an intermediate. The intermediate, dicumyl peroxide, and low-density polyethylene were mixed, melt-grafted, water-cooled, and granulated to obtain grafted modified low-density polyethylene.
3. The low-dielectric insulation material suitable for 10kV cables according to claim 2, characterized in that, The molar ratio of 3-aminobenzoic acid to dodecenylsuccinic anhydride is 1:(1.05~1.1).
4. A low-dielectric insulation material suitable for 10kV cables according to claim 2, characterized in that, The mass ratio of the intermediate, dicumyl peroxide, to low-density polyethylene is (8~12):(0.06~0.1):
100.
5. A low-dielectric insulation material suitable for 10kV cables according to claim 1, characterized in that, The preparation method of the modified nanoclay includes the following steps: Add octadecyl glycol polyethylene glycol ether to anhydrous ethanol and stir at 60-65°C; add nano-clay and ultrasonically disperse for 40-50 min; let stand for 1.5-2 h and then dry to obtain modified nano-clay.
6. A low-dielectric insulation material suitable for 10kV cables according to claim 5, characterized in that, The mass ratio of the octadecyl glycol polyethylene glycol ether to the nano-clay is (1.5~2):
100.
7. A low-dielectric insulating material suitable for 10kV cables according to claim 1, characterized in that, The silane-modified nano zinc oxide is prepared by modifying nano zinc oxide with a particle size of 10~50nm with vinyltrimethoxysilane.
8. A low-dielectric insulating material suitable for 10kV cables according to claim 1, characterized in that, The antioxidant is 4,4'-thiobis(2-tert-butyl-5-methylphenol) or 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].
9. A low-dielectric insulating material suitable for 10kV cables according to claim 1, characterized in that, The peroxide crosslinking agent is dicumyl peroxide; the lubricant is polyethylene wax.
10. A method for preparing a low-dielectric insulating material suitable for 10kV cables according to any one of claims 1 to 9, characterized in that, Includes the following steps: S1: Low-density polyethylene, grafted low-density polyethylene, modified nano clay, silane-modified nano zinc oxide, antioxidant and lubricant are put into a high-speed mixer and mixed at 60~80℃ for 5~10 minutes to obtain a premix. S2: The premixed material and peroxide crosslinking agent are added to a twin-screw extruder. The barrel temperature is 140~170℃ and the screw speed is 220~300rpm. After water cooling, pelletizing and drying, a low dielectric insulating material is obtained.
Citation Information
Patent Citations
Water-tree-resistant polyethylene insulation nano-composite material and preparation method thereof
CN104231395A
